2013
DOI: 10.1002/ajh.23423
|View full text |Cite
|
Sign up to set email alerts
|

Strikingly high false positivity of surveillance FDG‐PET/CT scanning among patients with diffuse large cell lymphoma in the rituximab era

Abstract: Predictive value (PV) of surveillance fluorodeoxyglucose positron emission tomography (FDG-PET) in patients with diffuse large B-cell lymphoma (DLBCL) treated with chemotherapy-rituximab (R) versus chemotherapy only, remains unclear. The aim of the current study was to compare the performance of surveillance PET in DLBCL patients receiving CHOP (cyclophosphamide, hydroxydaunorubicin hydrochloride, vincristine, and prednisone) alone versus CHOP-R. Institutional database was retrospectively searched for adults w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 36 publications
1
57
0
3
Order By: Relevance
“…11 However, our results are in agreement with the five previous studies that have failed to show a survival benefit when relapses are detected before development of symptoms or physical examination abnormalities. 11,12,14,25,31 Due to the small number of patients with asymptomatic relapse detected solely via surveillance scan in this cohort, we were unable to identify a subgroup of patients where surveillance may be useful. Determining the optimal follow-up strategy and potentially a group of patients where scans may be beneficial is difficult outside of a prospective, randomized trial.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…11 However, our results are in agreement with the five previous studies that have failed to show a survival benefit when relapses are detected before development of symptoms or physical examination abnormalities. 11,12,14,25,31 Due to the small number of patients with asymptomatic relapse detected solely via surveillance scan in this cohort, we were unable to identify a subgroup of patients where surveillance may be useful. Determining the optimal follow-up strategy and potentially a group of patients where scans may be beneficial is difficult outside of a prospective, randomized trial.…”
Section: Discussionmentioning
confidence: 75%
“…32 Imaging studies, particularly PET scans, may have false-positive results and lead to further testing including unnecessary biopsies. 20,25 Patients' quality of life may be negatively affected, as the anticipation of a scan is associated with increased anxiety levels for lymphoma survivors. 22 Lastly, imaging costs money.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, both studies had a major (12)(13)(14)(15). Posttreatment and follow-up 18 F-FDG PET/CT studies have a strikingly high number of false-positive results, as has been reported for several lymphoma subtypes (16)(17)(18)(19), including Hodgkin lymphoma (20). Consequently, the studies by Gallamini et al (12,13) are methodologically seriously biased.…”
Section: Replymentioning
confidence: 85%
“…Multivariate analysis showed rituximab administration was the most significant predictor of FP PET. 10 Guidelines state that PET should be avoided within 10 days of chemotherapy, 2 weeks of granulocyte-colony stimulating factor (G-CSF) treatment, or 3 months of radiotherapy in order to minimize false positives. 9 Allogeneic stem cell transplantation (alloSCT) can also result in persistent reactive FDG positivity.…”
Section: Current Controversiesmentioning
confidence: 99%